DEFFERAL PADA DONOR DARAH - Christina Roosarjani; Desi Mayasari; Titis Wahyuono (Jurnal Infokes, 2019)
Suspension of blood donor is an act of temporary deferral or permanent exclusion of blood donation because it is suspected or confirmed to have infectious diseases, hematological diseases, or other medical conditions that will be Affect your blood safety or affect your own donor health. The general purpose of this study is to determine the overview of suspension on blood donors. This type of observational analytical research with the crosssectional approach. The population of this study was a blood donor at the Indonesian Red Cross Surakarta City in June 2019 as many as 59 respondents. Sampling techniques using sample design. Data collection using secondary data and primary data. Univariate data analysis with frequency distribution table. The results of this research are mostly male blood donor, which is 48 respondents (81.4%), most of > 35 years as many as 45 respondents (76.3%) And most have blood group B as many as 25 respondents (33.9%) And blood donation that was lifted most of the blood donor detected HBV as much as 40 respondents (67.8%), HCV 2 respondents (3.4%), HIV 2 respondents (3.4%) And the TPHA 15 respondents (25.4%). The conclusion of this research is Donor blood that has been suspend most of the blood donor detected HBV as much as 40 respondents (67.8%), HCV 2 respondents (3.4%), HIV 2 respondents (3.4%) And the TPHA 15 respondents (25.4%).